Tradisi Balimau Kasai di Desa Air Tiris Sebagai Bentuk Komunikasi Dakwah dan Interaksi Sosial Antar Generasi - Muhamad Hizbullah; Saepullah Saepullah; Lili Rahmawati (Kopertais Wilayah I DKI Jakarta dan Banten, 2026)
This study aims to analyze how the Balimau Kasai tradition in Air Tiris Village functions as a medium for da’wah communication by employing the perspectives of Social Interaction theory and Kurt Lewin’s Field Dynamics theory. The analysis focuses on four aspects: the social environment, cultural structure, social change process, and intergenerational interaction. The method employed is qualitative research with a case study design, involving customary leaders, religious figures, female figures, and community members as purposively selected informants, through in-depth interviews, limited observation, and documentation study. The findings reveal that the social environment of Balimau Kasai creates an inclusive and religious interaction field, in which customary practices and Islamic values are closely intertwined in ritual stages such as grave visitation, tabligh akbar, donation for orphans, mandi balimau, and traditional games, thereby effectively serving as a vehicle for the internalization of da’wah values. Social changes resulting from education, migration, and modernization do not necessarily erode the tradition; rather, they encourage meaning negotiation and adjustments in its implementation. Meanwhile, intergenerational interaction ensures the transmission of spiritual, cultural, and Islamic da’wah values through dialogical and collaborative communication patterns. In conclusion, Balimau Kasai in Air Tiris represents an adaptive cultural da’wah model that remains firmly rooted in Malay Islamic identity, and Lewin’s theoretical framework proves effective in explaining the social dynamics that sustain the continuity of the tradition.